2016
DOI: 10.1038/cr.2016.111
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TRA2B-DNAH5 fusion as a novel oncogenic driver in human lung squamous cell carcinoma

Abstract: Lung squamous cell carcinoma (SCC) is one of the major subtypes of lung cancer. Our current knowledge of oncogenic drivers in this specific subtype of lung cancer is largely limited compared with lung adenocarcinoma (ADC). Through exon array analyses, molecular analyses and functional studies, we here identify the TRA2B-DNAH5 fusion as a novel oncogenic driver in lung SCC. We found that this gene fusion occurs exclusively in lung SCC (3.1%, 5/163), but not in lung ADC (0/119). Through mechanistic studies, we f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Tra2β has been proven to be upregulated in various types of cancer including lung squamous cell carcinoma, glioma cancer, and prostate cancer . Tra2β is involved in several important processes including cell proliferation, epithelial‐to‐mesenchymal transition, invasion, and metastasis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tra2β has been proven to be upregulated in various types of cancer including lung squamous cell carcinoma, glioma cancer, and prostate cancer . Tra2β is involved in several important processes including cell proliferation, epithelial‐to‐mesenchymal transition, invasion, and metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that Tra2β may be a prognostic parameter for LSCC and provides the possibility of using Tra2β in individualization of both patient prognosis and therapy. Tra2β has been proven to be upregulated in various types of cancer including lung squamous cell carcinoma, 36 glioma cancer, 14 and prostate cancer. 15 Tra2β is involved in several important processes including cell proliferation, epithelial-to-mesenchymal transition, invasion, and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…During the past few years, PEBP4 has been identified as a contributor to the development of numerous types of cancer (6)(7)(8)(9)20,21). Our previous study indicated that overexpression of PEBP4 enhances NSCLC cell proliferation and the invasive ability of cancer cells, while inhibiting apoptosis (9).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that a single nucleotide polymorphism in dynein axonemal heavy chain (DNAH5) could be related to hyperinflation in COPD patients 91 . Other authors have described that the oncogenic driver originated by the association of DNAH5 and transformer-2 protein homolog beta (TRA2B) genes might have a role in the development of squamous cell lung cancer 92 .…”
Section: Several Potential Pathogenic Mechanisms Could Explain the LImentioning
confidence: 99%